The Edinburgh companion to Scottish women's writing - Norquay, Glenda, 1958- (Edinburgh companions to Scottish literature., 2012)
Recognises the richness of women's contribution to Scottish literature. By combining historical spread with a thematic structure, this volume explores the ways in which gender has shaped literary output and addresses the changing situations in which women lived and wrote. It places the work of established writers such as Margaret Oliphant, Naomi Mitchison and A.L. Kennedy in new contexts and discusses the writing of critically neglected figures such as SÃƠleas na Ceapaich, Mary Queen of Scots, Anne Grant, Janet Hamilton, Isabella Bird, F. Marion McNeill and Denise Mina. There are chapters on women in Gaelic culture, women's relationship to oral traditions and to key literary periods, women's engagements with nationalism, with space, with genre fiction and with the activity of reading. Key features. * Includes innovative scholarship from leading critics of gender and Scottish Studies, including Sarah Dunnigan (Edinburgh), Carol Anderson (Open University), Pam Perkins (Manitoba), Florence Boos (Iowa) * Responds to current developments in the field of feminist and literary studies * Includes an authoritative introduction and a guide to further reading